Aqueous Biphasic Systems Composed of Cholinium Chloride and Polymers as Effective Platforms for the Purification of Recombinant Green Fluorescent Protein - Dos Santos, Nathalia V. [UNESP]; Martins, Margarida; Santos-Ebinuma, Valéria C. [UNESP]; Ventura, Sónia P. M.; Coutinho, Joaìo A. P.; Valentini, Sandro R. [UNESP]; Pereira, Jorge F. B. [UNESP] (American Chemical Society (ACS), 2018)
Green fluorescent protein (GFP) has excellent properties as a biosensor and biomarker; however, its widespread use is limited by its purification costs. Alternative low-cost purification techniques can overcome this issue. The aim of this work was to evaluate aqueous biphasic systems (ABS) composed of cholinium chloride ([Ch]Cl) and different polymers as effective platforms to recover GFP from cell lysate of recombinant Escherichia coli BL21. All systems completely extracted GFP from cell lysate (>99%) into the polymeric- or [Ch]Cl-rich phases. In general, [Ch]Cl-based ABS allowed a good purification capacity (GFP 80-100% pure), with the best results (approximately 100% pure GFP) achieved with a polypropylene glycol (PPG)-400/[Ch]Cl ABS in a single-step extraction or in a two-step extraction (back-extraction) by the integration of a polyethylene glycol (PEG)/sodium polyacrylate+[Ch]Cl ABS with a following stage using a PEG/[Ch]Cl-based ABS. Additionally, to demonstrate the potential of the PPG-400/[Ch]Cl ABS in downstream processing, solvent recycling and GFP polishing were carried out using ultrafiltration. Finally, the capacity of the PPG-400/[Ch]Cl ABS to extract other fluorescent proteins was also confirmed. The results clearly demonstrated that the PPG-400/[Ch]Cl ABS can be applied in downstream processing for the purification of proteins, not only enhancing purification yields but also providing simpler, quicker, cost-effective, and biocompatible processes.
Keywords: Aqueous biphasic systems; Cholinium chloride; Green fluorescent protein; Integrated downstream process; Purification